The Symbolic Meaning of Wedding Offerings in Buru Island - Risman Iye; Jafar Nurlatu; Susiati Susiati; Taufik Taufik; Harziko Harziko; Fithriyah Inda Nur Abida (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Buton, 2022)
The meaning of a marriage is the union between the two brides, namely a man and a woman. This research examines the symbolic meaning of the groom's surrender to the bride. The approach used in this study is a semantic approach. The semantic approach is an approach to see the form of speech and interpret the form of the speech or the meaning of symbols. In determining the source of data for research, it is based on the ability and skill of the researcher in trying to uncover a subjective event and determine the informant in accordance with the terms and conditions so that the data needed by the researcher is truly in accordance with nature or concrete facts. Data collection techniques carried out in this study were interviews, recording, notes, and documentation. Data analysis is a process of arranging data sequences, organizing them into patterns, categories, and basic units of description. The data that has been obtained through the recordings, then analyzed using descriptive methods, namely the depiction of the facts found as they are. The results of the study show that there are seven forms of offerings given by the groom, namely a. seserahan banana, b. seserahan betel leaf, c. seserahan ring, d. women's clothing e. traditional food and fruits, f. household furniture. g. surrender of money. Then from the meaning of the surrender, the two existing cultural values are, the social values contained in the handover ceremony at the Buru Island marriage and cultural values.